Use Of 3 Phase Electric Motors In Lifts Or Elevators - Deitje Sofie Pongoh; Brian Anugrah Nasana Putra Malonda; Daniel Jesilloh Audrey Karundeng; Mario Petro Poluan; Mikhael Meidy Junior Tumiwa (Publikasi Indonesia, 2025)
In the industrial world, induction motors are one of the most widely used types of electric motors to support the production process. Its popularity is due to several advantages, such as simple construction, relatively affordable prices, high efficiency, and minimal maintenance requirements compared to other types of motors. Three-phase induction motors have the characteristic of a fairly large starting current when first turned on. However, this problem can be minimized by various starting methods, such as the use of star-delta circuits, autotransformers, soft starters, and inverters (VFDs). Three-phase induction motors are the most common type of induction motor. Because of their affordable price and high efficiency, 3-phase induction motors are widely used in industry. The disadvantage of three-phase induction motors is that they cannot maintain a constant speed when the load changes rapidly due to their non-linear parameter characteristics.